Investigation of the Vibration Effects on an Outer Rotor Brushless Direct Current Motor - Ali Sinan Cabuk (IEEE Access)
Light electric vehicles used as scooters, electric bikes, tricycles and mini cars are mostly preferred today, especially in urban transportation. Outer rotor Brushless Direct Current Motor (BLDCM) is frequently used in the powertrain of light electric vehicles in terms of efficiency and reliable or appreciable torque per both developed power and weight densities. Nevertheless, the in-wheel BLDCM is sensitive to torque ripple and electromagnetic vibrations due to the imbalances of d-q-axis inductance. Vibration in in-wheel electric motors is one of the disruptive effects that affects both driving comfort and operating performance of the motor. This paper presents the experimental and simulation results of vibration effects on outer rotor BLDCM using ANSYS Workbench. The design model is obtained with the results of the electromagnetic analysis of the outer rotor BLDCM with 3kW power and 1000rpm speed, and random vibration and directional velocity analyzes were carried out in accordance with real operating conditions. The random and harmonic analysis of vibrations revealed that they create different vibration effects on the stator and rotor. Simulation results show that high vibrations occur in the stator and low vibrations occur in the rotor at low frequencies. The measurement results on the simulated design prototype are consistent with the simulation results and show that the vibration effect decreases with the increase in frequency.